THE POTENTIAL OF 3D-PRINTED CONSTRUCTION IN THE POST-WAR REBUILDING OF UKRAINE: ASSESSMENT OF IMPACT ON LANDSCAPE COMPONENTS - Зеленчук, Іван (SWorldJournal, 2024)
The possibility of solving the problems of rapid reconstruction of buildings and structures destroyed as a result of war; using the technology of 3D-printed construction was considered. The technological features and best practices of using 3D-printed co